1996
DOI: 10.1099/13500872-142-8-2245
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of the white phasespecific WH11 gene product of Candida albicans

Abstract: Cells of Candida albicans WO-1 switch frequently, spontaneously and reversibly between a white and opaque phase. The white-opaque transition involves the regulation of phase-specific genes. In the white budding phase, cells express the white phase-specific gene W H I I , which encodes a protein with homology to the heat shock protein Hspl2 of Saccharomyces cerevisiae. A recombinant Whl 1 protein has been synthesized, purified to apparent homogeneity and used to generate a rabbit polyclonal antiserum. The antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…There are reasons to believe that RLUC levels do indeed reflect transcriptional states. While stationary-phase cells and budding cells contain the Wh11 protein, as demonstrated by indirect immunofluorescent staining with anti-Wh11 antiserum, contain WH11 mRNA, and express RLUC when it is under the regulation of the Wh11 promoter, cells which have just extended a germ tube (i.e., an incipient hypha) are devoid of Wh11 antigen, do not contain WH11 mRNA, and contain dramatically reduced levels of RLUC activity when RLUC is under the regulation of the WH11 promoter (14,25). In addition, the relative levels of reporter transcript in the various deletion derivatives in the original promoter analysis (22) were highly similar to the relative levels of RLUC activity measured in the comparative deletion derivatives in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reasons to believe that RLUC levels do indeed reflect transcriptional states. While stationary-phase cells and budding cells contain the Wh11 protein, as demonstrated by indirect immunofluorescent staining with anti-Wh11 antiserum, contain WH11 mRNA, and express RLUC when it is under the regulation of the Wh11 promoter, cells which have just extended a germ tube (i.e., an incipient hypha) are devoid of Wh11 antigen, do not contain WH11 mRNA, and contain dramatically reduced levels of RLUC activity when RLUC is under the regulation of the WH11 promoter (14,25). In addition, the relative levels of reporter transcript in the various deletion derivatives in the original promoter analysis (22) were highly similar to the relative levels of RLUC activity measured in the comparative deletion derivatives in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that cells which formed buds at pH 4.5 contained both the WH11 transcript (25) and WH11 protein (14), but cells which formed hyphae at pH 6.7 contained neither transcript (25) nor protein (14). To characterize the kinetics of the loss of RLUC activity in a cell population induced to form hyphae, cells harboring the transcriptional fusion derivative pCRW5⌬6 were analyzed under the regime of pH-regulated dimorphism.…”
Section: Wh11mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years we (19 -24) and others (25)(26)(27)(28)(29)(30)(31)(32) have been investigating specific Ab induction as an immunotherapeutic preventive measure against the development of candidiasis. We have developed a vaccine for active immunization and have discovered protective mAbs; both approaches have shown efficacious promise against experimental, hematogenously disseminated candidiasis and against vaginal infection due to C. albicans.…”
mentioning
confidence: 99%
“…The WH11 gene encodes a protein with homology to the heat shock protein Hsp12 and is localized in the cytoplasm of white cells (33). The SAP genes encode secreted aspartic proteinases that have been shown to contribute to the virulence of WO-1 and other C. albicans strains (14,16).…”
mentioning
confidence: 99%